Entrepreneurial Spirit of Vegetable Vendors at Kliwon Market: A Competence Paradox Analysis - Gentur Ageng Sejati; Dumasari Dumasari; Sulistyani Budiningsih; Watemin Watemin (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
The agricultural sector remains a critical pillar of Indonesia's micro-economy. This study exhaustively analyzes the entrepreneurial spirit among Micro, Small, and Medium Enterprises (MSMEs), specifically vegetable vendors at Kliwon Market, Karanglewas. Furthermore, it identifies structural and psychological obstacles to business development. Employing a descriptive quantitative method, 75 respondents were selected via Cluster and Convenience Sampling. Findings reveal a "competence paradox": vendors exhibit high operational spirit (Responsibility 4.80, Self-Confidence 4.72) but significant strategic weaknesses (Risk-Taking 3.86). Internal obstacles, primarily a lack of innovation (34.7%), outweigh external factors. The study suggests that traditional market sustainability relies heavily on transforming vendor mindsets from survivalist to growth-oriented through financial literacy and collective supply chain efficiency.